2017
DOI: 10.1111/jam.13550
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipids and lactonic sophorolipids: natural antimicrobial surfactants for oral hygiene

Abstract: The findings indicate the potential value of biosurfactants for both oral hygiene and the pharmaceutical industries since there is a serious need to reduce the reliance on synthetic antimicrobials and antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 39 publications
0
51
0
4
Order By: Relevance
“…MIC of SLs was 32 µg mL −1 , and MIC of nisin was 0.5 µg mL −1 that was much lower than that of SLs (Table 1 and Figure 1). A much higher MIC (400 µg mL −1 ) of SLs was reported in suppressing S. aureus ATCC 29737 by Joshi-Navare [27] and S. aureus ATCC 14576 by Elshikh et al [28] The differences may be due to different test strains or SLs types, or different methods since culture plate method and microdilution method were used in studies of Joshi-Navare and Elshikh et al It has been reported that there were different activities of antibacterial compounds between in vitro and in vivo studies; for instance, the dosage in vivo could be much greater than the in vitro MICs obtained, and so is the SLs. [29] We studied the application of SLs in fresh milk and found good effects for milk preservation at the concentration of 500 µg mL −1 (data not shown).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…MIC of SLs was 32 µg mL −1 , and MIC of nisin was 0.5 µg mL −1 that was much lower than that of SLs (Table 1 and Figure 1). A much higher MIC (400 µg mL −1 ) of SLs was reported in suppressing S. aureus ATCC 29737 by Joshi-Navare [27] and S. aureus ATCC 14576 by Elshikh et al [28] The differences may be due to different test strains or SLs types, or different methods since culture plate method and microdilution method were used in studies of Joshi-Navare and Elshikh et al It has been reported that there were different activities of antibacterial compounds between in vitro and in vivo studies; for instance, the dosage in vivo could be much greater than the in vitro MICs obtained, and so is the SLs. [29] We studied the application of SLs in fresh milk and found good effects for milk preservation at the concentration of 500 µg mL −1 (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…MIC of SLs was 32 µg mL −1 , and MIC of nisin was 0.5 µg mL −1 that was much lower than that of SLs (Table and Figure ). A much higher MIC (400 µg mL −1 ) of SLs was reported in suppressing S. aureus ATCC 29737 by Joshi‐Navare and S. aureus ATCC 14576 by Elshikh et al . The differences may be due to different test strains or SLs types, or different methods since culture plate method and microdilution method were used in studies of Joshi‐Navare and Elshikh et al.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The evidence of the efficacy of different biosurfactants from different micro-organism in differing contexts remains a challenge. There is good evidence of the effectiveness of biosurfactants in terms of antimicrobial activity and there is increasing evidence of the benefits of biosurfactants in terms of wound healing, dermatological applications and oral care (Elshikh et al 2017b). There is promising work in the area of drug delivery but in the area of cancer treatment where biosurfactants might prove most efficacious there remains much conflicting data.…”
Section: Future Trends and Conclusionmentioning
confidence: 99%